Caring for Sekaten Traditions, Caring for Indonesia: Preserving Local Cultural Values in the Midst of Foreign Cultural Exposure - Willy Khadafi; Rahma Hayati Harahap (TALENTA Publisher, 2024)
Sekaten tradition is an ancestral cultural heritage that has lasted since the days of the Islamic Mataram Kingdom. This tradition holds a philosophical meaning about the relationship of man with the Creator through the Sekaten tradition. In addition, the Sekaten procession also reflects the spirit of mutual cooperation that is closely inherent in Javanese society. Unfortunately, in today's modern era, the enthusiasm of the younger generation towards Sekaten is fading. This may threaten the preservation of this tradition in the future. Efforts to revitalize Sekaten need to be done by exploring the philosophical values and local wisdom contained in it. This excavation is important so that the meaning of this tradition remains relevant for the millennial generation. In addition, it is necessary to socialize and assist young people to love and preserve Sekaten as a local cultural identity that should be maintained. The participation of all components of society is necessary in order to maintain the existence of Sekaten in the midst of modernization, so that ancestral values are maintained and timeless by the changing times.